The caffeine-sensitive calcium(2+) store in vascular smooth muscle. - Alexander, Peter. (University of Ottawa (Canada), 1994)
The objectives of this study were as follows: (1) to establish a technique to determine (Ca$\sp{2+}\rbrack\sb i$ in single enzymatically isolated vascular smooth muscle cells (VSMCs) from the rat tail artery by means of the fura-2 fluorescent dye, (2) to study the relationship between VSMC shortening and Ca$\sp{2+}$ mobilization by caffeine, (3) to determine the mechanism of caffeine-induced Ca$\sp{2+}$ mobilization by studying the effects of removal of extracellular Ca$\sp{2+}$ and agents that modulate Ca$\sp{2+}$ mobilization (ryanodine, TMB-8, nifedipine, thapsigargin), (4) to determine the possible physiological role of the caffeine-sensitive Ca$\sp{2+}$ store in VSMCs by its interaction with noradrenaline. We conclude that, the fura-2 technique may be successfully employed to measure (Ca$\sp{2+}\rbrack\sb i$ in single vascular smooth muscle cells from the rat tail artery. The (Ca$\sp{2+}\rbrack\sb i$ response was found to be reproducible irrespective of cell length. This is the first study to show this, although others have used single cells to study (Ca$\sp{2+}\rbrack\sb i$ changes, the question of whether cell morphology affects (Ca$\sp{2+}\rbrack\sb i$ has never been addressed. This allows comparative (Ca$\sp{2+}\rbrack\sb i$ studies to be performed on the same single vascular smooth muscle cell regardless of its contractile state. This is important as there can be great heterogeneity in the Ca$\sp{2+}$ signal response between different cells in the same population. On this basis, we have shown that ryanodine reduces the caffeine-induced Ca$\sp{2+}$ response; whereas other agents known to affect Ca$\sp{2+}$ regulation such as thapsigargin, TMB-8, and nifedipine had no effect on the caffeine-induced Ca$\sp{2+}$ response. Extracellular Ca$\sp{2+}$ was found to play an important role in the maintenance of resting and tonic (Ca$\sp{2+}\rbrack\sb i$ levels, as well as being essential to replenishment of the caffeine-sensitive Ca$\sp{2+}$ store. We have also shown that caffeine and noradrenaline are equally effective in releasing intracellular Ca$\sp{2+}$ and inducing a tonic increase in (Ca$\sp{2+}\rbrack\sb i.$ (Abstract shortened by UMI.)
Keywords: Biology, Cell.